Australia at an educational crossroads: special schools and inclusive education - Cumming, Therese M.; Jolly, Jennifer L.; Saint-James, Aaron (Frontiers in Education, 2024)
The ongoing debate surrounding special schools and inclusive education in Australia has come to the forefront since the recommendations of the 2023 Royal Commission into Violence, Abuse, Neglect and Exploitation of People with Disability, where the Commissioners were split on the implementation of full educational inclusion and the elimination of special schools. The authors discuss the controversy surrounding segregated special education classes and schools, particularly considering the push for full inclusion. The concept of inclusion is examined through a brief review of national and international policies and academic and popular literature, including how the inclusion continuum is conceptualized by policymakers, academics, and families. Stakeholder perspectives on the complexities and challenges of implementing full inclusion in mainstream school settings offer differing experiences and opinions on what is possible. Lastly, by examining the nuances of the special school controversy, the authors provide recommendations on how best to meet the educational needs of all students, across the spectrum of abilities.